Mathematical Language of Suku Abun in Tambraw Regency of Soutwest Papua - Rokhima, Nur (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The Abun tribe is located in Tambraw Province of Southwest Papua. There are a number of Abun tribal cultures that are closely related to the context of learning mathematics. However, educators in eastern Indonesia have not seen much of this culture as a context that can be used as a starting point in mathematics learning. Thus, this study aims to explore the mentioning of number words in the Abun tribal language that can be used as a starting point in mathematics learning. The study uses source ethnographic studies of library studies, field observations, and interviews with sources who understand the Abun tribal language well to clarify and/or provide greater understanding of the results of the literary study collected. The results of the research showed that there are a number of mathematical words used by the community of Tambraw in the Abun tribal language that can be used as a starting point in learning mathematics. This mathematical language includes the mentioning of numbers from 0 to 9